PENERAPAN MODEL PEMBELAJARAN INKUIRI DISERTAI MEDIA POWER POINT PADA MATERI POKOK STATISTIK - Suminto, Suminto (JURNAL e-DuMath, 2017)
Abstract : The objectives of the study were to find out the mean differences of the students learning outcomes of the experimental class and the control class, and to find out which of the higher mathematics learning outcomes of the students in the experimental class and control class. The research population of the students of class VIII odd semester of SMP N 1 Kalirejo in the academic year 2015-2016. The sample of this research is taken by cluster random sampling technique. Learning results obtained through tests with 5 items about the essay. Data analysis was done by normality test, homogeneity test. The samples are normally distributed and homogeneous, followed by t-test. From the result of data analysis, it is obtained the average of learning result of math student of experimental class 77,52 and control class 70,64. Conclusion There is difference of mean of result of learning of student mathematics in experiment class and control class. And the average result of the students learning of math experiment class is bigger than the average of mathematics learning result of the control class student. Keywords: Learning, inquiry with media pawer point